Model Probabilistik Penentuan Bobot Biaya Tenaga Kerja, Material, dan Peralatan pada Proyek Gedung Menggunakan Simulasi Monte Carlo - Henry Maurice; Mardiaman Mardiaman (Jurnal Talenta Sipil, 2026)
The construction industry is characterized by high cost uncertainty due to material price fluctuations, labor productivity variability, design changes, and market dynamics. At the conceptual estimating stage, project cost structures are commonly determined using deterministic approaches based on historical averages, which fail to adequately represent real-world variability. This study aims to develop a probabilistic model for determining the weight of labor, material, and equipment costs in three-story building projects using Monte Carlo simulation based on empirical data from 16 completed projects. The methodology includes descriptive statistical analysis to obtain distribution parameters, goodness-of-fit testing for selecting appropriate probability distributions, and a 1,000-iteration Monte Carlo simulation applied to a normalized composite cost structure index. The results indicate average cost proportions of 40.57% for labor, 34.53% for materials, and 11.45% for equipment, with substantial variation across projects. The simulation produced a mean composite index value of 116.98 with a P10–P90 interval ranging from 74.25 to 157.30, indicating moderate to high cost uncertainty. The proposed model is recommended as a confidence-level–based conceptual estimating baseline to enhance budget planning accuracy and cost risk management in low-rise building projects.